An Ordinance, for the Government of the Powder Magazine of this City, and for other purposes (12 Feb.1828, Richmond, VA) - (:unkn) unknown (General Publisher, 1828)
That no person or persons within the City of Richmond, shall retain in his, her or their possession at any time, more than twenty-five pounds of Powder.
--
Keywords: GUN POWDER STORAGE